Sensing Self and Non-Self DNA by Innate Immune Receptors and Their Signaling Pathways - Sok, Sophia Ping Meow; Ori, Daisuke; Nagoor, Noor Hasima; Kawai, Taro (Begell House, 2018)
The innate immune system serves as the first line of defense to protect the host from pathogen infection. As a first step, the pattern recognition receptors (PRRs) recognize pathogen-associated molecular patterns (PAMPs), such as non-self DNA derived from pathogens, and damage-associated molecular patterns (DAMPs), such as self DNA released from damaged or injured cells. Sensing of such DNAs elicits innate immune responses through the production of type I interferons (IFNs) and proinflammatory cytokines resulting from the activation of interferon regulatory factor 3 (IRF3) and nuclear factor kappa B (NF-κB), respectively. These cytokines are key players in interlinking innate and adaptive immune responses. However, defects in DNA sensors and their signaling cascades lead to dysregulation of immune responses, autoimmune diseases, and cancer progression. Here we provide an update on DNA signaling pathways in response to pathogen infection and cell injury, and on the roles of regulators in governing the immune system and maintaining host homeostasis. We also discuss the evasion of immunosurveillance by pathogens.